Callus Induction of Aerides odorata Lour. by Adding 2,4 Dichlorophenoxyacetic Acid (2,4-D) - Azharia Khalida; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2019)
The research about callus induction of Aerides odorata L. by adding 2,4 Dichlorophenoxyacetic Acid (2,4-D), has been done from August to October 2018 in Plant Physiology and Tissue Culture Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Andalas University, Padang. The aim of this research was found the effective consentration of 2,4-D to induce somatic embryo of A.odorata. The research used Completely Randomized Design (CRD) with 5 treatments and 6 replications. The treatments were: 0 mg/L 2,4-D; 0,25 mg/L 2,4-D; 0,5 mg/L 2,4-D; 0,75 mg/L 2,4-D; 1 mg/L 2,4-D. The result showed that the treatmeant were able induction callus of A.odorata, with compact until the friable texture, color of the resulting callus is yellowish green and greenish yellow. 2,4-D 1 mg/L was the best concentration to increase fresh weight of callus.